Grade III Spontaneous Rectus Sheath Hematoma Concomitant to SLE - Tutak, Ayse Sahin; Findikli, Huseyin Avni; Aslan, Sefer; Tastekin, Esin (Archives of Clinical and Medical Case Reports, 2018)
Rectus sheath hematoma is defined as the accumulation of blood within the rectus sheath caused by tears in the epigastric arteries or the rectus muscle fibres. Although seen rarely, the use of anti-coagulants has been held responsible as the most common predisposing factor in the etiology of autoimmuune diseases. Systemic lupus erythematosus (SLE) is a disease which is challenging in diagnosis and management both in respect of multiple clinical responses to the disease and various complications. Hemorrhagic markers have a place in the clinical manifestation of the disease. The case is here presented of a 78-year old male patient who was admitted to the Intensive Care Unit (ICU) with a diagnosis of pneumonia, and during hospitalisation was diagnosed with SLE and rectus sheath hematoma. The points which can be discussed in this case are that there was no history of anticoagulant use, and despite the coagulation function test results in the normal range and the order of low-dose (40 mg/day) enoxiparin sodium as thromboembolism prophylaxis in the first 2 days of admittance, this is the first reported case of spontaneous giant rectus sheath hematoma where SLE was held responsible as an etiological factor.